(untitled) (International Journal of Communication Systems and Network Technologies, 2018)
Paper is outcome of DGS inspired antenna which was proposed for the WLAN applications of S band. Proposed antenna is designed at 1.8GHz frequency. DGS of split ring shaped structure was implemented later to modify the antenna characteristics. Modified results increases the return loss up to -37dB from -12dB and increased the bandwidth to 41.4MHz from 38MMHz.